A Methionine-Restricted Diet and Endurance Exercise Decrease Bone Mass and Extrinsic Strength but Increase Intrinsic Strength in Growing Male Rats. Issue 5 (19th March 2014) - Huang, Tsang-Hai; Lewis, Jack L.; Lin, Hsin-Shih; Kuo, Liang-Tong; Mao, Shih-Wei; Tai, Yuh-Shiou; Chang, Ming-Shi; Ables, Gene P.; Perrone, Carmen E.; Yang, Rong-Sen
Abstract: Dietary methionine restriction (MR) has been suggested to be comparable to endurance exercise with respect to its beneficial effects on health. To further investigate the effects of MR and endurance exercise on growing bone, 7-wk-old male Sprague-Dawley rats were fed different L-methionine (Met)-containing diets with or without endurance exercise intervention (Ex; 0.86% Met, 0.52% Met, 0.17% Met, 0.86% Met-Ex, 0.52% Met-Ex, and 0.17% Met-Ex groups). After an 8-wk intervention period, exercise-trained rats had a 9.2% lower body weight (BW) than did sedentary rats ( P < 0.05). Additionally, 0.17% Met–fed rats had 32% lower BW when compared with rats fed the other 2 diets ( P < 0.05). Serum osteocalcin was lower in the 0.17% Met-Ex group compared with the other 2 exercise groups and the 0.17% Met group ( P < 0.05). Serum concentrations of C-terminal telopeptide of type 1 collagen were lower in exercise-trained and 0.17% Met–fed rats than in sedentary rats and rats fed the other 2 diets ( P < 0.05 for both). Rats fed the 0.17% Met diet had lower trabecular bone volume, bone mineralization activities, and bone mineral content (BMC; e.g., total, cortical, and spongy BMC) and bone mineral density (BMD; e.g., total and spongy BMD) indices compared with rats fed the other 2 diets ( P < 0.05). Exercise-trained rats also had lower bone mineralization activity, trabecular osteoclast density, total BMC, cortical BMC, and total BMD compared with sedentary rats ( P < 0.05). In total BMD, only the 0.17% Met-Ex group had values lower than the other 2 exercise groups and the 0.17% Met group ( P < 0.05). Compared with rats fed the other 2 diets and sedentary rats, the femora of 0.17% Met–fed and exercise-trained rats, respectively, had smaller size and/or lower extrinsic strength but enhanced intrinsic biomechanical properties ( P < 0.05). The results indicate that MR and endurance exercise caused lower whole bone mass, size, and/or strength but might enhance intrinsic bone strength.